Kamias (Averrhoa Bilimbi), Starfruit (Averrhoa Carambola), and Karamay (Phyllanthus Acidus) Fruit Extract as Alternative Stain Remover - Jurish Pauleen Hitalia; Yca Justerine Bringuelo; Ivan Henry Jordan; Edward Martinez; Remo Leba Jr.; Anamarie G. Vadez; Hassanal Abusama; Alan Paculanan (ASEAN Journal of Science and Engineering, 2021)
This study generally aimed to determine the effectiveness of kamias, star fruit, and karamay fruit extracts in removing stains. Previous studies revealed the effectiveness of Kamias as a stain remover, while, this study compared the effectiveness of different fruit extracts as a stain remover and the potential utilization of other fruit extracts from trees that are locally available.  We determined the cost of making stain remover using kamias, karamay, and star fruit extracts, the ability of these fruit extracts as a stain remover in terms of the degree of strain reduction and whitening of the cloth, and ultimately, the significant difference between the various treatments. Results revealed that the use of star fruit extract was the cheapest among the four treatments while the highest cost was incurred using Karamay extract. There was a significant difference observed between treatments. Bleach was the most effective in removing the stains and whitening the fabric, followed by the kamias extract. In terms of removing stains, whitening the cloth, and availability in the neighborhood, the extract was found to have the best results. We, therefore, recommended the use of kamias extract as an alternative organic stain remover for fabrics and be used by the households. Being derived from natural fruit extract and contain no dangerous chemicals, the product is safe for human use and environment-friendly.